Dual-axis solar energy tracking and monitoring system with Arduino as a microcontroller / Siti Sufiah Abd Wahid, Mohd Sufian Ramli and Nur Idayu Zabidin - Abd Wahid, Siti Sufiah; Ramli, Mohd Sufian; Zabidin, Nur Idayu (Research Management Institute (RMI), 2023)
As an inexhaustible and non-polluting energy source of the future, solar energy is improving to meet the world's ever-increasing energy demands. In this project, the solar panel is made movable to absorb energy in different directions based on the direction of the sun to maximize the amount of energy generated by solar photovoltaic system. Four Light Dependent Resistors (LDRs), a voltage sensor and a set of humidity and temperature sensor are acting as inputs. Meanwhile, two servo motor outputs are placed in the horizontal and vertical axes to maximize power absorption by orienting the PV panel towards the varying sun directions. The Arduino Mega2560 was used as the microcontroller that controls the inputs to make sure the outputs are operating as required. Apart from the servo motors, another important feature of the project includes the monitoring unit for the system which comprises of the LCD display and Microsoft Excel Data Streamer.